Vaccine effectiveness of JCOVDEN single-dose against COVID-19 hospitalisation in Europe: An id.DRIVE test-negative case-control study - Chloé Wyndham-Thomas; E. Claire Newbern; Ainara Mira-Iglesias; Akshat Dwivedi; Alejandro Orrico Sánchez; Andrés Antón; Charlotte Martin; Giancarlo Icardi; Irma Casas; Kok Yew Ngew; Laura Drikite; Leonie de Munter; et al. (Journal of Infection and Public Health)
Background: JCOVDEN (Ad26.COV2.S), a viral-vector vaccine, was granted conditional marketing authorisation in the European Union for the prevention of COVID-19 in early 2021. We present JCOVDEN single-dose vaccine effectiveness (VE) estimates against COVID-19 hospitalisation. Methods: The id.DRIVE (previously COVIDRIVE) COVID-19 VE study is an ongoing European non-interventional, multi-centre study with a test-negative case-control design. Study participants were adults ≥ 18 years old, hospitalised with severe acute respiratory infection between 1 May 2021 and 28 February 2023. Estimated as a single measure over the entire study period, VE was stratified by risk group, time since vaccination intervals (14 days-12 weeks, 12-to-25 weeks, 25-to-52 weeks, >52 weeks), SARS-CoV-2 variant and calendar time categories. All estimates were adjusted for symptom-onset date, age, sex, and number of pre-defined chronic conditions. Results: Overall, VE was 55.6 % (95 % CI 23.6; 74.2) for a median time since vaccination of 146 days. For 18- to 49-year-olds, VE was 61.6 % (95 % CI 16.2; 82.4), 57.7 % (95 % CI 3.4; 81.5) for 50- to-64-years-olds, and 40.8 % (95 % CI −6.0; 66.9) for ≥ 65-year-olds. Most precise estimates were obtained for time since vaccination 12-to- 25-week interval (59.2 % [95 % CI 25.0; 77.8]) and for the calendar time period 1 Aug 2021 −30 Nov 2021 (Delta predominant; 51.2 % [95 % CI 21.7; 69.6]). Conclusion: The JCOVDEN single-dose protected against COVID-19 hospitalisation. It is effective for at least six months, with VE estimates comparatively lower in the older age groups. Results had low to medium levels of certainty and are to be interpreted with caution.